The Heart of the Current Reception of the Ecclesiology of the People of God. "New paths in the theology and practice of sensus fidei" - Rafael Luciani (Warszawskie Studia Teologiczne)
The current synodal process is fostering a deepening of the sensus fidei, as a precious theological treasure in the listening of the Spirit on the part of the People of God. It supposes an ecclesiological turn, which has its novelty in the intertwined reading of Lumen gentium 12 (sensus fidei) and 23 (local Churches). It foresees a new reception of pneumatology and a spiritual and binding dynamic of all the faithful, and introduces restitutio (or giving back) as a new step on the way to build the sensus totius populi. We are living an ecclesial stage in which a first emergence of what will be a synodal ecclesiality can be appreciated, though not fully yet theorized. We will try to develop this in the following contribution.